Kajian Yuridis Diskresi Kepolisian Dalam Hal Pembelaan Diri Terhadap Pelaku Kejahatan - Herman Herman; Patahillah Asba; Iswandy Rani Saputra (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2023)
This research was conducted to find out how the use of police discretion against criminals who resisted and to find out what factors influenced the police's discretionary action taken by the police in the Pinrang district. The type of research used in this research is normative and empirical research. The results of this study indicate that the Use of Police Discretion must refer to laws and regulations both in the Police Act and the Protap Kapolri Number 1 of 2010 concerning the prevention of anarchism, where the police can take decisive action in the form of shots that can paralyze the perpetrators if the actions of the perpetrators can harm members police and society. The use of discretion is not an authority, but police actions that must be accounted for based on applicable laws and norms as well as the factors that cause police discretion to be exercised, namely the perpetrators do not heed the appeals of members in the field such as warning shots and calls for surrender or the perpetrators put up resistance against members or the public. that's there.